Agro-industrial waste: a low cost adsorbent for effective removal of 4-chloro-2-methylphenoxyacetic acid herbicide in batch and packed bed modes - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2016)
The present work describes the aqueous phase removal of 4-chloro-2-methylphenoxyacetic acid herbicide by rice husk ash (RHA) using batch and packed bed adsorption techniques. The effects of dosage, initial concentration, time, pH, temperature, and particle size of adsorbent in batch compared with effects of influent concentration, flow rate, and bed height in packed bed were studied. The particle size effect reveals that the removal is dependent on chemical composition (silica and carbon content) together with BET surface area of RHA. The aptness of Langmuir isotherm to batch data indicates the favorable adsorption whereas that of Temkin isotherm informs the heterogeneous nature of RHA. The kinetics of adsorption follows the pseudo-second order and Elovich models while thermodynamics of process indicates the exothermic adsorption. Among the models applied in packed bed study, the deactivation kinetic, Yoon-Nelson and bed depth service time (BDST) models are suitable to explain the packed bed adsorption. The adsorption capacity of RHA in packed bed study is found greater than that in batch. The adsorption capacity of RHA determined by the BDST model is 3019 mg/L for 90 % saturation of bed. The adsorption capacity of RHA based on weight is similar to 2.3 times and that based on surface area is similar to 55.55 times greater than that of granular activated carbon.